Immanuel Kant's philosophy and the reconstruction of Polish philosophy at the turn of the 20th century - Kuliniak, Radosław (Studia z Historii Filozofii, 2024)
The revival of Polish philosophy, after more than a century of partitions, took place at the turn of the 19th and 20th centuries. At that time, thanks to Wincenty Lutosławski, a correspondent at Kant-Studien, a stimulus was given to the fossilised and dispersed Polish philosophical community. The necessary reforms were spearheaded by Henryk Struve, Władysław Weryho, and Kazimierz Twarddowski. They became animators of philosophical life, establishing Przegląd Filozoficzny, the Polish Philosophical Society in Lviv and prompting the first Polish translations of Kant’s works. Through them, the reforms initiated deepened throughout the period up to the restoration of independence and later in free Poland. Kant’s philosophy became one of the pillars of these reforms. Thanks to them, a new kind of philosophical thinking took shape in Poland, marked by Kantian criticism.